Comparison of antimicrobial susceptibility among Clostridium difficile isolated from an integrated human and swine population in Texas - Norman, Keri N.; Scott, Harvey Morgan; Harvey, Roger B.; Norby, Bo; Hume, Michael E. (My University, 2014)
Clostridium difficile can be a major problem in hospitals because the bacterium primarily affects individuals with an altered intestinal flora; this largely occurs through prolonged antibiotic use. Proposed sources of increased community-acquired infections are food animals and retail meats. The objective of this study was to compare the antimicrobial resistance patterns of C. difficile isolated from a closed, integrated population of humans and swine to increase understanding of the bacterium in these populations. Swine fecal samples were collected from a vertically flowing swine population consisting of farrowing, nursery, breeding, and grower/finisher production groups. Human wastewater samples were collected from swine worker and non-worker occupational group cohorts. Antimicrobial susceptibility testing was performed on 523 C. difficile strains from the population using commercially available agar diffusion Epsilometer test (Etest®) for 11 different antimicrobials. All of the swine and human strains were susceptible to amoxicillin/clavulanic acid, piperacillin/tazobactam, and vancomycin. In addition, all the human strains were susceptible to chloramphenicol. The majority of the human and swine strains were resistant to cefoxitin and ciprofloxacin. Statistically significant differences in antimicrobial susceptibility were found among the swine production groups for ciprofloxacin, tetracycline, amoxicillin/clavulanic acid, and clindamycin. No significant differences in antimicrobial susceptibility were found across human occupational group cohorts. We found that 8.3% of the swine strains and 13.3% of the human strains exhibited resistance to metronidazole. The finding of differences in susceptibility patterns between human and swine strains of C. difficile, provides evidence that transmission between host species in this integrated population is unlikely.
Keywords: Clostridium difficile; Intestinal flora; Antimicrobial resistance; Antimicrobial susceptibility